Contrast use in image-guided procedures: Balancing Diagnostic Quality and Patient Safety - Sharahili, Rami Moraya; Malawi, Ola Ali; Aldawudi, Batoul Hussain; Alofi, Nawaf Eid; Althuneyyan, Moath Abdullah; Al-Hussain , Ghadah Omair; Albalawi, Faisel Ahmed (Journal of Posthumanism, 2024)
The use of contrast agents in image-guided procedures has significantly improved diagnostic capabilities by enhancing visualization of internal structures, enabling earlier and more accurate detection of pathologies. Contrast medium can be used in different imaging modalities, such as X-rays, ultrasound, computed tomography (CT), and magnetic resonance imaging (MRI). Currently, various types of contrast media are available such as iodine-based, gadolinium-based, barium sulfate agents, microbubbles, and nanoparticles agents. Despite their diagnostic benefits, these agents may lead to serious side effects, posing risks to patient safety and healthcare systems. These adverse effects represent a burden on healthcare systems. The aim of this review is to explore the diagnostic value and adverse effects of contrast media in various settings, and to discuss strategies that can balance contrast use in image-guided procedures diagnostic value with patient safety. Contrast medium has shown effectiveness in diagnosing various diseases including tumors, abscesses, and inflammatory diseases (e.g. Crohn’s). However, these agents were linked to multiple side effects, most importantly contrast-induced acute kidney injury and hypersensitivity (early and delayed). A collaborative, multidisciplinary approach involving radiologists, nurses, pharmacists, and allergy specialists should be implemented for optimizing outcomes and minimizing risks.